Polnische und deutsche Phraseologismen mit den Komponenten kot/Katze und pies/Hund im "Słownik języka polskiego" von Samuel Bogumił Linde und im "Deutschen Wörterbuch" von Jacob und Wilhelm Grimm - Dominika Janus (Linguistik Online, 2015)
The aim of the article is to analyze Polish and German idioms containing names of animals, namely cat and dog in Słownik języka polskiego by Samuel Bogumił Linde and Deutsches Wörterbuch by Jacob and Wilhelm Grimm. Firstly, it is to be stated how many of those idioms mentioned in both of the dictionaries have survived and how many are extinct. The meanings, symbols and images hidden in the idioms regarded as the historical ones seem to be particularly interesting. The last point of the analysis refers to the fact of how much Polish and German idioms containing the same names of animals are similar.